1995
DOI: 10.1021/jo00110a035
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Directed Regioselective Radical Cyclization Leading to .beta.-Lactams: Formal Synthesis of (.+-.)-PS-5 and (+)-Thienamycin

Abstract: A new method for the synthesis of p-lactams by tributyltin hydride (Bu3SnH)-mediated radical cyclizations of N-ethenyl-a-bromo amides bearing sulfur-substituent(s) a t the terminus of the N-vinylic bond is described. N-[2-(Phenylthio)ethenyll-a-bromoacetamide (1 11, upon treatment with BuaSnH in the presence of azobis(isobutyronitri1e) (AIBN) in boiling toluene, underwent radical cyclization in a 4-exo-trig manner to give p-lactam 13, but in low yield (22%), whereas N-[2,2-bis-(pheny1thio)ethenyll congener 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…7 To screen for catalytic activity, we performed the reactions under the following defined conditions: 90 mM of donor, 130 mM of acceptor and 9 mol% antibody in PBS (pH¼7.4) at room temperature. Control experiments revealed that, in the absence of antibody, no reactions take place under these conditions (entries 1,3,5,7,9). For the antibody-mediated reactions, we found that all the reactions were taking place in the presence of ab84G3 with the exception of the reaction of acetone with 2-phenylthiobutyraldehyde 8 (entry 10).…”
Section: Resultsmentioning
confidence: 77%
“…7 To screen for catalytic activity, we performed the reactions under the following defined conditions: 90 mM of donor, 130 mM of acceptor and 9 mol% antibody in PBS (pH¼7.4) at room temperature. Control experiments revealed that, in the absence of antibody, no reactions take place under these conditions (entries 1,3,5,7,9). For the antibody-mediated reactions, we found that all the reactions were taking place in the presence of ab84G3 with the exception of the reaction of acetone with 2-phenylthiobutyraldehyde 8 (entry 10).…”
Section: Resultsmentioning
confidence: 77%
“…These intermediates would rapidly equilibrate, and hydrogen atom abstraction from the thiol by the less hindered radical C , according to the precedent of Montevecchi and co-workers,9 should afford cis -β-thioenamide D as the kinetic product. In contrast, known methods of β-thioenamide construction based on imine acylation10 or Pummerer rearrangement11 chemistry deliver predominantly the trans isomers. We also recognized that the presence of excess thiol in the reaction mixture would permit isomerization of D to the thermodynamically more stable trans isomer via a radical addition–β-thiyl radical elimination pathway 12.…”
mentioning
confidence: 99%
“…The substitution reaction between aryl thiol 1 and bromoacetaldehyde acetal 16 was performed in the presence of one equivalent of sodium ethoxide. Acidic hydrolysis of the dimethyl acetal 17 yielded aldehyde 18, [41] which was then converted into oxime 19. Sulfone 20 was prepared by oxidation with oxone, and then the oxime moiety was reduced to N-hydroxyethylamine 21 using sodium cyanoborohydride at room temperature.…”
Section: Resultsmentioning
confidence: 99%